Seletividade de herbicidas na cultura de crambe - Ferreira Souza, Guilherme Sasso [UNESP]; Vitorino, Hermeson dos Santos; Costa Lara Fioreze, Ana Carolina da; Rocha Pereira, Maria Renata [UNESP]; Martins, Dagoberto [UNESP] (Univ Estadual Londrina, 2014)
The low productivity of crambe can be associated with many factors, among these, the competition with weeds, which reduces the yield, harvest affects and contributes to the increase in seed moisture. Therefore, this study aimed to evaluate the tolerance of crambe plants cv. FMS Brilhante to herbicides applied in preplant incorporated (PPI), preemergence (PRE), and postemergence (POST). The study was installed in a green-house and the treatments consisted of the herbicide application in: pre-plant incorporated ofdiclosulam, flumetsulam, metribuzin, and trifluralin; preemergence applicationof atrazine, diclosulam, diuron, flumetsulam, metribuzim, S-metolachlor, sulfentrazone, and trifluralin; and postemergence application ofbentazon, carfentrazone-ethyl, clefoxydim, cletodim + fenoxaprop-p-ethyl, ethoxysulfuron, fomesafen, fluazifop-p-butyl, flumioxazin, halosulfuron, imazamox, imazapic, lactofen, nicosulfuron, oxadiazon, quinclorac, and setoxydim. Visual evaluations of phytotoxicity on crambe plants were realized after applications, the seedlings were counted and the height and plant dry matter were determined in the end of the evaluation period. In conditions where the studies were conducted, we can conclude that only the trifluralin application in PRE and the application of clefoxidim+fenoxaprop-p-ethyl, fluazifop-p-butyl, quinclorac, setoxydim and clefoxydim in POST showed selectivity and potential use for FMS Brilhante crambe cultivar.
Selectivity of herbicides in crambe crop
Keywords: Crambe abyssinica; application mode; phytotoxicity; phytointoxication